The effectiveness of using riddle game on vocabulary mastery of the ninth graders at MTs Ma’arif NU 1 Ajibarang Banyumas (Conference on English Language Teaching, 2025)
Vocabulary mastery is a crucial aspect for enhancing skills in listening, speaking, reading, and writing. Effective learning techniques play a vital role in helping students achieve their learning goals. One such technique, the riddle game, is used to examine its impact on students’ vocabulary mastery and their learning outcomes. This study investigates the effectiveness of using riddle games on vocabulary mastery among Grade IX students at MTs Ma’arif NU 1 Ajibarang Banyumas. The total population consisted of 68 students from three classes. Using simple random sampling, 25 students from class IX-A and 24 students from class IX-B were selected. A quantitative approach was applied, with data collected through pre-tests and post-tests in multiple-choice format. A t-test was conducted to assess potential differences in average scores between the experimental and control groups. Initially, both groups had low pre-test scores, with mean scores of 69.9 (experimental) and 63.4 (control). After the intervention, the experimental group achieved a higher post-test mean score of 83.4, compared to 71.1 in the control group. The research also showed a Sig. 2-tailed (p) value of 0.004, less than the alpha (α) of 0.05, leading to the rejection of H0 and acceptance of H1. The findings highlighted the potential of riddle games to improve vocabulary mastery in an enjoyable and effective way. Students in the experimental group showed improved ability to understand and apply vocabulary in context. This underscores the value of creative techniques to support language learning.